Viscoelasticity of basal plasma membranes and cortices derived from MDCK II cells - Janshoff, Andreas (Biophysical reports, 2021)
The mechanical properties of cells are largely determined by the architecture and dynamics of their viscoelastic cortex, which consists of a contractile, cross-linked actin mesh attached to the plasma membrane via linker proteins. Measuring the mechanical properties of adherent, polarized epithelial cells is usually limited to the upper, i.e., apical side, of the cells because of their accessibility on culture dishes. Therefore, less is known about the viscoelastic properties of basal membranes. Here, I investigate the viscoelastic properties of basolateral membranes derived from polarized MDCK II epithelia in response to external deformation and compare them to living cells probed at the apical side. MDCK II cells were grown on porous surfaces to confluence, and the upper cell body was removed via a squirting-lysis protocol. The free-standing, defoliated basal membranes were subject to force indentation and relaxation experiments permitting a precise assessment of cortical viscoelasticity. A new theoretical framework to describe the force cycles is developed and applied to obtain the time-dependent area compressibility modulus of cell cortices from adherent cells. Compared with the viscoelastic response of living cells, the basolateral membranes are substantially less fluid and stiffer but obey to the same universal scaling law if excess area is taken correctly into account. [Display omitted]